An Unusual Case of Double Heterotopic Pancreatic Tissues in the Same Localization - Kalkan, İsmail Hakkı and Öztaş, Erkin and Suvak, Burak and Yildiz, Hakan and Beyazit, Yavuz and Ibiş, Mehmet (JOP. Journal of the Pancreas, 2012)
No abstract available.